Radiation dose metrics in multidetector computed tomography examinations: A multicentre retrospective study from seven tertiary care hospitals in Kerala, South India - Varghese, Binoj; Kandanga, Indu; Puthussery, Paul; Vijayan, Dhanesh; Babu, S P Harish; Aneesh, M K; Noufal, Muhammad; Binu, E V; Babu, Arun C; James, Sheen M; Kumar, Siva (Indian Journal of Radiology and Imaging, 2018)
Background: Presently, computed tomography (CT) is the most important source of medical radiation exposure. CT radiation doses vary considerably across institutions depending on the protocol and make of equipment. India does not yet have national or region-specific CT diagnostic reference levels. Aim: To evaluate radiation doses of consecutive multidetector CT (MDCT) examinations based on anatomic region, performed in 1 month, collected simultaneously from seven tertiary care hospitals in Kerala. Settings and Design: Descriptive study. Materials and Methods: We collected the CT radiation dose data of examinations from the seven collaborating tertiary care hospitals in Kerala, performed with MDCT scanners of five different makes. The data included anatomic region, number of phases, CT dose index (CTDIvol), dose-length product (DLP), and effective dose (ED) of each examinations and patient demographic data. Statistical Analysis: We calculated the 25th, 50th, and 75th percentiles of the CTDIvol, DLP, and ED according to anatomic region. We made descriptive comparisons of these results with corresponding data from other countries. Results: Of 3553 patients, head was the most frequently performed examination (60%), followed by abdomen (19%). For single-phase head examinations, 75th percentile of CTDIvolwas 68.1 mGy, DLP 1120 mGy-cm, and ED 2.1 mSv. The 75th percentiles of CTDIvol, DLP, and ED for single-phase abdomen examinations were 10.6, 509.3, and 7.7, and multiphase examinations were 14.6, 2666.9, and 40.8; single-phase chest examinations were 23.4, 916.7, and 13.38, and multiphase examinations were 19.9, 1737.6, and 25.36; single-phase neck were 24.9, 733.6, and 3.814, and multiphase neck were 24.9, 2076, and 10.79, respectively. Conclusion: This summary CT radiation dose data of most frequently performed anatomical regions could provide a starting point for institutional analysis of CT radiation doses, which in turn leads to meaningful optimization of CT.
Keywords: Achievable dose; CT dose index; diagnostic reference level; diagnostic reference range; dose-length product; effective dose; radiation dose metrics